Green Tourism Investment and Collaborative Governance Plus Multi-Helix: A Digital Policy Network Analysis - Andi Yudha Pranata; Andy Fefta Wijaya; Imam Hanafi; Hermawan Hermawan (JURNAL AKTA, 2026)
Green tourism investment is being encouraged more and more as a way to balance economic growth from tourism with protecting the environment; however, it often faces challenges due to disorganized institutions, unequal power dynamics, and a focus on marketing rather than meaningful discussion. In areas with decentralized governance, partnerships between government, businesses, communities, universities, and media are often set up but not always put into practice effectively, leading to questions about whether green tourism truly changes how things are governed or just serves as a way to make it look beneficial. This study examines green tourism investment governance in Batu City, East Java, Indonesia, using the Collaborative Governance Plus Multi-Helix (CGPMH) framework. A qualitative explanatory methodology employing a non-intrusive research design was utilized. The data utilized were sourced from two official tourism Instagram accounts from 2024 to 2025, in addition to internet press coverage. Miles, Huberman, and Saldaña created an interactive qualitative analysis model that was used to look at the data. This approach involves the collection, condensation, presentation, and formulation of conclusions, complemented by lexicon-based sentiment analysis and policy network analysis. The results suggest that collaborative governance is still structurally centralistic. Green tourism is utilized more as a way to talk and support than as a way to talk about issues that can divide power and define sustainability priorities.